From unipolar to tripolar world - Virmani, Arvind (New Delhi, 2010)
Developed country experts on international affairs and the global economy have consistently underestimated the speed with which China's economy and power would rise relative to Germany, Japan and the USA. They are now similarly underestimating the speed at which India's economy will close the economic size and power gaps. This book shows, why and how a tri-polar global power structure will emerge from the current confused system variously described as 'multipolar', 'apolar', 'pluripolar', 'West and the rest' and 'unipolar with an oligopolistic fringe'. The Book goes on to draw out the implications and consequences of this evolving global power structure and makes suggestions on the policy options that need to be explored and pursued to increase the possibility of a peaceful transformation.
Keywords: International economic relations